The Analysis of Length-weight Relationship of Channa punctatus with Relative Physico-chemical Parameters - Naseem Jhan2, Ramesh Chandra1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract The present observations stated that the growth of Channa affected due to the pollution of water. In the clear water the growth was good i.e. 1.89% in compression to polluted water i.e.1.05%.The DO was also decline in polluted water i.e from 8.14 to 2.34 mg/l. Â Key words: Channa, length, weight, water quality 1Department of Zoology, S.S. (P.G.) College, Shahjahanpur, U.P. India; 2RKS Degree College Sahawar, Kanshiramnagar, U.P. India Please Cite This Article As: Ramesh Chandra and Naseem Jhan. 2010. The Analysis of Length-weight Relationship of Channa punctatus with Relative Physico-chemical Parameters. J. Exp. Sci. 1(5):4-5. Â